Factors affecting the occupancy of Chinese pangolins (Manis pentadactyla) suggest a highly specialized ecological niche. Issue 1 (26th January 2023) - Dhami, Bijaya; Neupane, Bijaya; Devkota, Bishnu Prasad; Maraseni, Tek; Sadadev, Bipana Maiya; Bista, Shreyashi; Adhikari, Amit; Chhetri, Nar Bahadur; Panta, Melina; Stewart, Alyssa B.
Abstract: The Chinese pangolin is a critically endangered and biologically unique species, yet information on its status, distribution, and habitat preferences is still scarce in Nepal, which limits effective conservation action. This study identified the current burrow density status, distribution pattern, and important habitat parameters associated with Chinese pangolin distribution in Nepal through opportunistic field surveys. Fifty‐four belt transects were examined for the presence of pangolin burrows. For each active burrow (burrow with freshly dug soil, footprints, and scat near the entrance) and old burrow (burrow with compacted soil, presence of dead leaves, and spider web in the entrance), we recorded the geographic coordinates and assessed data on 11 habitat parameters that included elevation, aspect, slope, canopy cover, ground cover, presence or absence of ant and termite colonies, habitat type, soil type, and distances to the nearest water source, road, and settlement. A total of 141 active burrows and 430 old burrows were recorded with an overall clumped distribution S 2 / a = 2.188 $$ \left\{\left(S^2/a\right)=2.188\right\} $$ . Active burrow density was estimated to be 1.04 burrows/ha. Of the 11 habitat parameters predicted to influence the probability of encountering pangolin burrows, all parameters were significant except elevation. More than 92% of the burrows were found at elevations between 450 and 750 m and facing either the SE or NW aspect. Similarly, about 90% of the burrows were distributed in areas having slopes between 0% and 30% with moderate to high canopy and ground cover, and located close to water sources, roads, and settlements. Additionally, they strongly preferred forest habitats (with Shorea robusta, Castanopsis indica, Schima wallichii, Clerodendron infortunatum, and Nephrolepis auriculata as the dominant vegetation), areas with red soil, and areas located near ant and termite colonies. Although the study area currently provides suitable habitat for Chinese pangolins, it is slowly being degraded due to increasing rates of forest degradation. Conservation efforts should be increased in order to protect this critically endangered species and their preferred habitats. Finally, our findings reveal the preferred habitat characteristics of Chinese pangolins, which could be instrumental for policy makers and forest managers in making conservation plans for Chinese pangolins.